Quality and Type of Chemical of Groundwater at Coastal Areas of Semarang - Purnama, Setyawan (Universitas Muhammadiyah Surakarta, 2004)
There are two objectives of this researh. First, to identify and analyze the condition of ground water quality in the research area, and second to determined the chemial types of groundwater. To ahieve these objectives 59 groundwater samples were taken stratifiedly, base on the different of electrical conductance value. As a result, it is identified that most groundwater in the research area is not suitable for drinking water sources, because has high concentration of electrical conductance, turbidity, hardness, chloride, manganese, and salinity. Thiis conclusion is also supported by stiff diagram analysis. The result of Stuyfzand analysis shhows that the chemical types of groundwater is very variative. Groundwater in coastal areas has higher suply of saline water than fresh water.